Pediatric robotic and reconstructive urology : a comprehensive guide - Gundeti, Mohan S. (Hoboken : John Wiley & Sons, 2012)
The most exciting contemporary developments in pediatric urology are now demonstrated in text and on video in this innovative, practical guide. A practical text for experienced practitioners and trainees alike, this comprehensive resource introduces the new techniques and surgical planning required to begin mastery of robotic approaches. From a renowned editor and contributors, this book features 130 illustrations and comes with a companion website containing 30 high-quality surgical videos demonstrating each technique.
31 Seminal Vesical Cyst ExcisionPart III: Adult Reconstructive Principles Applicable to Pediatrics; 32 Robotic NOTES (Natural Orifice Transluminal Endoscopic Surgery) in Adults: Limitations in the Pediatric Population; 33 Laparoendoscopic Single-Site (LESS) Surgery and Robotic Laparoendoscopic Single-Site (R-LESS) Surgery in Urology: Adult and Pediatric Applications; 34 Robotics in Adrenal Disease; 35 Alternative Techniques of Pyeloplasty in the Adult Population; 36 Ureteral Defects and Ureterovaginal Fistulas; 37 Robotic Reconstruction Techniques Following Cystectomy.
Part IV: Complications, Outcomes, and Future Perspective.
Print version record.
Keywords: Urinary organs -- Surgery; Pediatric urology; Children -- Surgery; Robotics in medicine; Adolescent; Child; Infant; Reconstructive Surgical Procedures -- methods; Robotics -- methods; Surgery, Computer-Assisted -- methods; Urologic Diseases -- surgery; Urologic Surgical Procedures -- methods; Medicine; Children -- Surgery; Pediatric urology; Robotics in medicine; Urinary organs -- Surgery; Electronic books